2022
DOI: 10.3390/land11081262
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Patterns of Urban Land Use Structure in Small Towns in China

Abstract: This study analyzes the spatial and temporal characteristics of urban land use structure of more than 18,000 small towns in China by using the National Urban Land Use Survey Data between 2009 and 2013. It finds that the urban land area of small towns expanded rapidly during the research period. The spatial pattern of urban land use structure in small towns exhibits significant regional differences. Small towns in developed coastal regions, particularly those located in global urban areas, have a higher urban l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The government's policy system is an important driving factor for the formation and evolution of land space development and the protection pattern in urban agglomeration areas [62,63], and it has a profound impact on the deterioration or improvement trend of eco-environmental quality [64,65]. This study found that with the implementation and adjustment of national and local government policies, the eco-environmental quality of the GPUA showed marked stage change characteristics.…”
Section: Government's Policy System and Eco-environmental Quality In ...mentioning
confidence: 81%
“…The government's policy system is an important driving factor for the formation and evolution of land space development and the protection pattern in urban agglomeration areas [62,63], and it has a profound impact on the deterioration or improvement trend of eco-environmental quality [64,65]. This study found that with the implementation and adjustment of national and local government policies, the eco-environmental quality of the GPUA showed marked stage change characteristics.…”
Section: Government's Policy System and Eco-environmental Quality In ...mentioning
confidence: 81%
“…The global Moran's I was used to test whether the spatial phenomenon has a clustering effect on the YRB [ 42 ]. where: is the number of cities; and is the CCDUU between cities and cities ; is the spatial weight value between cities and cities ; and is the mean and standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…The area of urban construction land in China surged from 6720 km 2 in 1981 to 58,307.7 km 2 in 2019, showing significant exponential growth and a rapid expansion trend. As a result, a series of problems have arisen, such as spatial sprawl, inefficient land use, increasingly tense relations between people and land, and escalating environmental pollution [3]. These changes have directly affected sustainable development and the quality of the living environment in the city.…”
Section: Introductionmentioning
confidence: 99%